First Total Synthesis of Artekeiskeanol A, C and Altissimacoumarin D - Talakokkula, Anil; Baikadi, Karunakar; Narsaiah, A. Venkat (SynOpen, 2019)
The total syntheses of artekeiskeanol A and C, and altissimacoumarin D have been achieved. The syntheses commenced from commercially available starting materials, 2,4-dihydroxybenzaldehyde and geraniol. The key steps involve Wittig and Riley oxidation reactions.
Keywords: geronyl; scopoletin; isofraxidin; altissimacoumarin; artekeiskeanol